Liquid-liquid phase separation-driven enzyme catalysis for efficient biosynthesis of isoprenoid natural products - Han Wang; Bing-Bing Ma; Fei Cao; Ji-Jin Xie; Bei-Bei Wang; Shao-Yong Zhang; Ji-Dong Wang; Zha-Jun Zhan; Yu-Mei Ge; Xu-Ming Mao (Science China Life Sciences, 2026)

La-mediated green rust for synergistic nitrogen–phosphorus removal and targeted N2 formation regulated by built-in electric field and spin state - Yibo Zhang; Jun Nan; Chen Liang; Zhencheng Ge; Han Deng; Yanhan Che; Yunhao Pan; Meng Li; Bohan Liu (Water Research, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Differential remediation of tetracycline vs. sulfamethoxazole-contaminated soils by ZVI/BC: Impacts on rice growth, soil properties, and key regulatory factors - Xu Su; Jie Han; Xuanming Wang; Siyu Wang; Yixuan Chen; Ziyi Ge; Jun Meng (Journal of Environmental Chemical Engineering, 2026)

Alleviating effects and mechanism of Lacticaseibacillus paracasei BHP06 on the allergic reactions induced by ovalbumin - Xiang-Ge Xin; Yue Meng; Jun Meng; Jun Xi; Chang-He Ding; Rui-Han Ge; Yu-Tong Bai; Ming-He Li (Food Bioscience, 2026)

A fast powerful X-ray transient from possible tidal disruption of a white dwarf - Dongyue Li; Wenda Zhang; Jun Yang; Jin-Hong Chen; Weimin Yuan; Huaqing Cheng; Fan Xu; Xinwen Shu; Rong-Feng Shen; Ning Jiang; Jiazheng Zhu; Chang Zhou; et al. (Science Bulletin, 2026)

Recyclable Na-Mn-O nanocomposite for dual-modal photothermal/ROS antibacterial therapy against multidrug-resistant bacteria in pathogen-laden wastewater - Zhi-ru Tao; Shu-xian Hou; Yi-mei Wang; Xue-chao Shi; Xin-xin Liu; Jun Ge; Yu-han Ji; Ya-qi Cheng; Zi-yi Leng; Xin-yv Cao; Rong-rong Li; Jin-nan Xuan; et al. (Journal of Water Process Engineering, 2026)

Valorization of blueberry pomace and red mud to zero valent iron biochar for antibiotic degradation with diminishment of toxic reagents - Xu Su; Jie Han; Yuwei Huang; Xuanming Wang; Siyu Wang; Ziyi Ge; Hechong Yuan; Juying Liu; Xuerong Xiang; Fan Xia; Li Lin; Yu Lan; et al. (Bioresource Technology, 2025)

Fs–LA–ICP–MS U–Pb dating of fluorite and its prospect for geological application - Yan-Wen Tang; Na Liu; Jun-Jie Han; Yan Liu; Wan-Ting Ge; Jian-Feng Gao; Ting-Guang Lan (Chemical Geology, 2025)

Mechanistic insight into enhancement of undissolved rice husk biochar on Tetracycline biodegradation by strain Serratia marcescens basing on electron transfer response - Siyu Wang; Jie Han; Ziyi Ge; Xu Su; Yongjia Shi; Fan Xia; Yuwei Huang; Jun Meng (Journal of Hazardous Materials, 2025)

Differential size-dependent response patterns and antibiotic resistance development mechanism in anammox consortia - Na-Na Han; Jun-Hui Yang; Ge-Ge Wu; Jia-Hui Yang; Jing-Ao Jin; Nian-Si Fan; Ren-Cun Jin (Journal of Hazardous Materials, 2025)

Foxp3 inhibits PCV2 replication by reducing the ATPase activity of Rep - Ruijiao Jiang; Qiuyan Huang; Ruiting Shen; Yongning Zhang; Lei Zhou; Xinna Ge; Jun Han; Xin Guo; Hanchun Yang (Veterinary Microbiology, 2025)

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

Pseudorabies virus inhibits the unfolded protein response for viral replication during the late stages of infection - Peng Gao; Jianle Ren; Qiongqiong Zhou; Peng Chen; Ailin Zhang; Yongning Zhang; Lei Zhou; Xinna Ge; Xin Guo; Jun Han; Hanchun Yang (Veterinary Microbiology, 2025)

Electrostatic repellent dispersion method for green and cost-effective aqueous radiative cooling paint - Jipeng Fei; Di Han; Kai Zhou; See Wee Koh; Junyu Ge; Jun Yan Tan; Bing Feng Ng; Zhong Chen; Lili Cai; Hong Li (Building and Environment, 2025)

Three-dimensional oriented Ca nanoporous carbon with N doping tuned via self-assembly to potentiate P adsorption: The vital role of the micro interfacial electronic environment - Yibo Zhang; Jun Nan; Fangmin Wu; Xuesong Ye; Zhencheng Ge; Li He; Yanhan Che; Han Deng; Yunhao Pan; Bohan Liu (Journal of Cleaner Production, 2025)

PRRSV infection inhibits CSFV C-strain replication via GSDMD-mediated pyroptosis - Ruijiao Jiang; Dengjin Chen; Yongning Zhang; Lei Zhou; Xinna Ge; Jun Han; Xin Guo; Hanchun Yang (Veterinary Microbiology, 2024)

Identifying modifiable factors and their joint effect on frailty: a large population-based prospective cohort study - Ling-Zhi Ma; Yi-Jun Ge; Yi Zhang; Xi-Han Cui; Jian-Feng Feng; Wei Cheng; Lan Tan; Jin-Tai Yu (GeroScience, 2024)

Anti-obesity effects of Lactiplantibacillus plantarum BHP03 on high-fat diet mice and its regulatory function on intestinal microbiota - Jun Meng; Pan-Pan Dong; Meng-Xi Zhu; Zheng Zhang; Jia-Hui Chen; Yue Meng; Chang-He Ding; Han Du; Dong-Ge Zheng; Ling-Guang Du (Food Bioscience, 2024)

A pH-responsive MOFs@MPN nanocarrier with enhancing antifungal activity for sustainable controlling myclobutanil release - Yushan Hou; Yaowei Zhang; Yanyan Huang; Ailing Zhou; Jiatong Han; Kexin Yang; Yiming Zhao; Jie Zhou; Jing Wang; Ge Chen; Xiaomin Xu; Donghui Xu; et al. (Chemical Engineering Journal, 2024)

Significant influence of urban human activities and marine input on rainwater chemistry in a coastal large city, China - Jie Zeng; Guilin Han; Qixin Wu; Rui Qu; Qing Ma; Jingwen Chen; Shijun Mao; Xin Ge; Zhong-Jun Wang; Zhiheng Ma (Water Research, 2024)

Evolution and determinants of precipitation chemistry in a plateau city, China: Insight from the pollutants source identification and environmental effect - Jie Zeng; Guilin Han; Qixin Wu; Qing Ma; Shijun Mao; Xin Ge; Zhong-Jun Wang; Chao Yang (Urban Climate, 2024)

Biotransformation characteristics of tetracycline by strain Serratia marcescens MSM2304 and its mechanism evaluation based on products analysis and genomics - Siyu Wang; Jie Han; Ziyi Ge; Xu Su; Yixuan Chen; Jun Meng (Journal of Environmental Management, 2024)

Infection of PRRSV inhibits CSFV C-strain replication by inducing macrophages polarization to M1 - Tianbei Tuo; Dengjin Chen; Lihong Wang; Yongning Zhang; Lei Zhou; Xinna Ge; Jun Han; Xin Guo; Hanchun Yang (Veterinary Microbiology, 2024)

Chemical evolution of rainfall in China's first eco-civilization demonstration city: Implication for the provenance identification of pollutants and rainwater acid neutralization - Jie Zeng; Guilin Han; Qixin Wu; Meixue Peng; Xin Ge; Shijun Mao; Zhong-Jun Wang; Qing Ma (Science of The Total Environment, 2024)

Morphological and phylogenetic analyses reveal a new species of Anthracophyllum (Omphalotaceae, Agaricales) in Zhejiang Province, China - Wen-Juan Yang; Miao Xu; Jing Zhang; Fan Zhou; Zhi-Fang Le; Wen-Jun Tong; Hai-Yan Song; Zhuo-Han Jin; Qiu-Ge Cheng; Jian-Ping Zhou; Yang Gao; Zhi-Jun Zhai; et al. (Archives of Microbiology, 2024)

Engineering of zeolitic imidazolate frameworks based on magnetic three-dimensional graphene as effective and reusable adsorbent to enhance the adsorption and removal of caffeine from tea samples - Yuwei Hua; Guangyang Liu; Zhihao Lin; Zhou Jie; Chenxi Zhao; Jiatong Han; Ge Chen; Linyun Li; Xiaodong Huang; Zhongxiao Liu; Jun Lv; Donghui Xu (Food Chemistry, 2024)

Effects of nutrients and light in aquatic habitat on the growth of Hydrocotyle vulgaris when expanded from terrestrial to aquatic habitat - Zhi-Huan Chen; Rui Zhang; Jun-Cai Xin; Zi-Han Qian; Shu-Jie Wang; Shang-Yan Qiu; Xue-Ge He; Chao Si (Aquatic Botany, 2024)

PRRSV inhibited the proliferation of CSFV by inducing IL-1β maturation via NLRP3 inflammasome activation - Dengjin Chen; Tianbei Tuo; Yongning Zhang; Lei Zhou; Xinna Ge; Jun Han; Xin Guo; Hanchun Yang (Veterinary Microbiology, 2023)

“Mini-community” simulation revealed the differences of endophytic fungal communities between the above- and below-ground tissues of Ephedra sinica Stapf - Xi Liu; Jin-Long Cui; Zhong-Ya Zhou; Zong-Bao Zhang; Xuan-Ge Cui; Bo Han; Jun-Hong Wang; Meng-Liang Wang; Yi-Min Li (Fungal Biology, 2023)

AIWW: a new nutrition-screening tool for the oncologic population - Yi-Zhong Ge; Zhen-Ming Fu; Qi Zhang; Meng-Meng Song; Guo-Tian Ruan; Xi Zhang; Xiao-Wei Zhang; Xiang-Rui Li; Kang-Ping Zhang; Meng Tang; Xiao-Yue Liu; Ming Yang; et al. (Science China Life Sciences, 2023)

Effective adsorption and removal of malachite green and Pb2+ from aqueous samples and fruit juices by pollen–inspired magnetic hydroxyapatite nanoparticles/hydrogel beads - Yuwei Hua; Donghui Xu; Zhongxiao Liu; Jie Zhou; Jiatong Han; Zhihao Lin; Dan Xu; Ge Chen; Xiaodong Huang; Jing Chen; Jun Lv; Guangyang Liu (Journal of Cleaner Production, 2023)

Microplastics exacerbate co-occurrence and horizontal transfer of antibiotic resistance genes - Xi Yu; Zhen-Chao Zhou; Xin-yi Shuai; Ze-jun Lin; Zhe Liu; Jin-yu Zhou; Yan-han Lin; Guang-shu Zeng; Zi-ye Ge; Hong Chen (Journal of Hazardous Materials, 2023)

Seeing the forest and the trees: Holistic view of social distancing on the spread of COVID-19 in China - Danlin Yu; Yaojun Zhang; Jun Meng; Xiaoxi Wang; Linfeng He; Meng Jia; Jie Ouyang; Yu Han; Ge Zhang; Yao Lu (Applied Geography, 2023)

Surprising leopard restoration in fragmented ecosystems reveals connections as the secret to conservation success - Fu Yanwen; Zhao Guojing; Dai Wenqian; Wang Yue; Li Jiawei; Tan Mengyu; Li Yan; Liu Haoran; Xie Bing; Jin Xiao; Fan Enyu; Zhao Lulu; et al. (Science of The Total Environment, 2023)

Genome-wide signatures of the geographic expansion and breeding of soybean - Ying-Hui Li; Chao Qin; Li Wang; Chengzhi Jiao; Huilong Hong; Yu Tian; Yanfei Li; Guangnan Xing; Jun Wang; Yongzhe Gu; Xingpeng Gao; Delin Li; et al. (Science China Life Sciences, 2023)

Shift work and nonalcoholic fatty liver disease incidence among Chinese rail workers: a 4-year longitudinal cohort study - Jiahui Xu; Shu Ni; Yuming Wang; Mengfan Yan; Xueli Yang; Han Ge; Zizhuo Jia; Ze Yang; Anqi Shan; Huanyu Liu; Nai-jun Tang (International Archives of Occupational and Environmental Health, 2023)

Rare taxa maintain the stability of crop mycobiomes and ecosystem functions - Chao Xiong; Ji‐Zheng He; Brajesh K. Singh; Yong‐Guan Zhu; Jun‐Tao Wang; Pei‐Pei Li; Qin‐Bing Zhang; Li‐Li Han; Ju‐Pei Shen; An‐Hui Ge; Chuan‐Fa Wu; Li‐Mei Zhang (Environmental Microbiology, 2021)
Summary Plants harbour highly diverse mycobiomes which sustain essential functions for host health and productivity. However, ecological processes that govern the plant–mycobiome assembly, interactions and their impact on ecosystem functions remain poorly known. Here we characterized the ecological role and community assembly of both abundant and rare fungal taxa along the soil–plant continuums (rhizosphere, phyllosphere and endosphere) in the maize–wheat/barley rotation system under different fertilization practices at two contrasting sites. Our results indicate that mycobiome assembly is shaped predominantly by compartment niche and host species rather than by environmental factors. Moreover, crop‐associated fungal communities are dominated by few abundant taxa mainly belonging to Sordariomycetes and Dothideomycetes, while the majority of diversity within mycobiomes are represented by rare taxa. For plant compartments, the abundant sub‐community is mainly determined by stochastic processes. In contrast, the rare sub‐community is more sensitive to host selection and mainly governed by deterministic processes. Furthermore, our results demonstrate that rare taxa play an important role in fungal co‐occurrence network and ecosystem functioning like crop yield and soil enzyme activities. These results significantly advance our understanding of crop mycobiome assembly and highlight the key role of rare taxa in sustaining the stability of crop mycobiomes and ecosystem functions.

Identification and evaluation of tobacco cytoplasmic male sterile line Nta(gla)S K326 generated from asymmetric protoplast fusion of Nicotiana glauca and N. tabacum followed by backcrossing with N. tabacum K326 - Xue-Jun Chen; Zhi-Jun Tong; Bing-Guang Xiao; Yong-Ping Li; Fang-Chan Jiao; Yong Li; Tao Pang; Dun-Huang Fang; Xing-Fu Wu; Yi-Han Zhang; He Xie; Ge Bai; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

A strategy for introducing an endangered plant Mosla hangchowensis to urban area based on nitrogen preference - Mei-Ying Fan; Kai-Xuan Pan; Wen-Juan Han; Yi-Jun Lu; Qi Shen; Meng Wang; Yuan Ren; Ze-Long Qu; Jie Chang; Ying Ge (Acta Physiologiae Plantarum, 2016)

Cloning and expression of floral organ development-related genes in herbaceous peony (Paeonia lactiflora Pall.) - Jintao Ge; Daqiu Zhao; Chenxia Han; Jing Wang; Zhaojun Hao; Jun Tao (Molecular Biology Reports, 2014)

Flower color diversity revealed by differential expression of flavonoid biosynthetic genes and flavonoid accumulation in herbaceous peony (Paeonia lactiflora Pall.) - Daqiu Zhao; Jun Tao; Chenxia Han; Jintao Ge (Molecular Biology Reports, 2012)

Time-dependent expression and distribution of Egr-1 during skeletal muscle wound healing in rats - Yan-Yan Fan; Guang-Hua Ye; Ke-Zhi Lin; Lin-Sheng Yu; Shu-Zhen Wu; Miao-Wu Dong; Jun-Ge Han; Xiang-Ping Feng; Xing-Biao Li (Journal of Molecular Histology, 2012)